A STUDY ON THE ANXIETY OF THE LOW AND HIGH SPEAKING ACHIEVERS OF THE ENGLISH EDUCATION DEPARTMENT OF UNIVERSITY OF ISLAM MALANG - Fahmi Arifin; Yahya Alaydrus; Eko Suhartoyo (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2020)
Abstract: This current research focused on identifying the contributing factors of students’ anxiety and to describe the type of anxiety that faced by low and high speaking achievers. This study used descriptive qualitative research method. The result of this research showed that both categorized students placed at “anxious” (low speaking achievers) and “mildly anxious” (high speaking achievers). It also gives a description that anxious students do not have a low score and mildly anxious students may not always have a good score. In this research, 2 anxious students are having a bit lower score from the other students, meanwhile 2 other students with mildly anxious having satisfactory score. The percentage of students’ response was also classed into three type of anxiety. 33.3% of students experienced communicative apprehension, whereas 30.3% feel anxious in test anxiety, and 36.4% of them were getting anxious in fear of negative evaluation. The last type of anxiety got the highest percentage. Keywords: anxiety, low speaking achiever, high speaking achiever